2015
DOI: 10.1002/cjce.22160
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modelling study of propane aromatization over H‐ZSM‐5 catalysts prepared by different silica sources

Abstract: The catalytic performance of H‐ZSM‐5 samples prepared from different silica sources, namely, Ludox (sample A), waterglass (sample B) and tetraethyl orthosilicate (sample C) in aromatization of propane was studied. The catalysts were characterized by BET, SEM, XRD and NH3‐TPD techniques to analyze the structure and acidity of the active sites. The performance tests were carried out in fixed‐bed reactor at 550 °C. For a quantitative assessment, the long‐term propane conversion data were fitted with a second orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…% Zn over HZSM-5 catalyst in the propane aromatization led to an increase in the deactivation constant from 0.0056 to 0.025 h -1 . By comparing the obtained deactivation constant value (Table IV) with Baradaran et al 35 results, it can be concluded that the increasing of deactivation constant is due to the increase of Zn load from 0.4 to 3 wt. %.…”
Section: Kinetic Modelling Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…% Zn over HZSM-5 catalyst in the propane aromatization led to an increase in the deactivation constant from 0.0056 to 0.025 h -1 . By comparing the obtained deactivation constant value (Table IV) with Baradaran et al 35 results, it can be concluded that the increasing of deactivation constant is due to the increase of Zn load from 0.4 to 3 wt. %.…”
Section: Kinetic Modelling Resultsmentioning
confidence: 56%
“…In comparison with the values of the reported activation energies for the propane aromatization, 23 the results obtained from this work are acceptable. It has been shown by Baradaran et al 35 that introducing of 0.4 wt. % Zn over HZSM-5 catalyst in the propane aromatization led to an increase in the deactivation constant from 0.0056 to 0.025 h -1 .…”
Section: Kinetic Modelling Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, recent research efforts are focused on catalyst development for BTX production from alternative feedstocks such as light alkanes. 4 Moreover, rapid progress has been made recently in utilizing stranded natural gas reserves for converting gas to liquid using a non-oxidative methane dehydroaromatization (DHA) catalytic route whereby the conventional gas-to-liquid (GTL) technologies become economically unaffordable. 5 The major challenges experienced so far in its implementation are the thermodynamic barrier, which limits the benzene yield to 12−13% at 700 °C, and rapid catalyst deactivation as a result of coke accumulation on the surface of the catalyst, which accounts for 10−20% methane conversion when the Mo/H-ZSM-5 catalyst is employed.…”
Section: Introductionmentioning
confidence: 99%
“…As it was alluded in many papers, the good operation of zeolites is under different factors, some of which are metals as promoter and acidity of the zeolites. The aromatization of some alkanes were studied meticulously by the authors of this manuscript [9][10][11]. The first aim of this work is scrutinizing the influence of the factors mentioned above over aromatization processes in order to comprehend how various catalysts conditions can make a change in the production of aromatic components.…”
Section: Introductionmentioning
confidence: 99%